KEAKURATAN KODE DIAGNOSIS FRAKTUR DAN EXTERNAL CAUSES DI RSUD MARDI WALUYO KOTA BLITAR - Nurhadi Nurhadi; Krisnita Dwi Jayanti; Andra Dwitama Hidayat; Sevi Oktrianadewi; Eva Firdayanti Bisono; Endah Retnani Wismaningsih; Elok Rizma Hapsari; Wahyu Wijaya Widiyanto (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
Diagnostic codification must fulfill 10 characteristics of quality data, namely one of which is accurate, namely the truth and validity of data values. External Causes are external causes of fracture cases which classify based on the place and activity of the incident. It is very important that external causes codes are documented in medical record files for financing analysis, health services and reporting. The purpose of this study was to determine the accuracy of the fracture diagnosis code and external causes at Mardi Waluyo Hospital, Blitar City in 2021. The research method used a retrospective descriptive. The sampling technique is simple random sampling, with 52 samples. The implementation of coding at Mardi Waluyo Hospital, Blitar City, was carried out by coder officers and was in accordance with the policies and standard operating procedures at the hospital. The level of accuracy of the fracture diagnosis code with a percentage of 85% is included in the category that needs improvement and external causes with a percentage of 6% is included in the unsatisfactory category. The inaccuracy of the external causes code is caused by the use of the 5th character or the activity code that has not yet been coded. The inaccuracy of the officers in coding caused the resulting code to be inaccurate, so it was suggested that filling out medical record documents must be filled in completely and clearly to support proper and accurate coding of fractures and external causes so as to produce a better percentage of accuracy.